Description of a contemporary pathogenic Escherichia coli isolated from pigs with post-weaning diarrhea in the United States from 2010 to 2023 - Rodrigo C. Paiva; Eric R. Burrough; Nubia Macedo; Ana Paula S. P. Silva; Maud de Lagarde; John M. Fairbrother; Pablo E. Piñeiro; Marcelo N. Almeida (Veterinary Research)
Abstract Post-weaning diarrhea (PWD) due to Escherichia coli in pigs is a significant enteric disease in the U.S. Contemporary data about the main virulence factors, colony morphology, and distribution of virotypes of isolates associated with post-weaning colibacillosis (PWC) is essential information for swine veterinarians, producers, and stakeholders. This study reports the rate of PWC/PWD, frequency of detection of fimbrial types, pathotypes, toxins, virotypes, morphological characteristics, and temporal analysis of the most prevalent virotype of enterotoxigenic E. coli recovered from cases of PWD in pigs in the United States. There was a significant increase in PWC cases submitted to the diagnostic laboratory in 2013, 2014, and 2021, respectively. A greater frequency of detection of F18 fimbrial adhesin (69.87%) was observed compared to F4 (26.19%), F5 (0.25%), F41 (0.13%), AIDA (0.10%), and multiple adhesins (3.46%), respectively. Hybrid ETEC:STEC pathotype was greater than ETEC and STEC, and STb toxin was present in 93.33% of the detected isolates. The most frequently observed virotype was F18:LT:STa:STb:Stx2e (27.71%). Smooth:mucoid colony morphology was associated with a greater likelihood of PWC (0.758, 0.968, and 0.993) compared to smooth, intermediate, and rough, respectively. The frequency of the F18:LT:STa:STb:Stx2e virotype increased across all U.S. states from 2016 to 2023, greatest in the northwest and east of Iowa and northeast Indiana in 2022 and Iowa in 2023. The virulence factors and morphology of enterotoxigenic E. coli associated with PWC across different states in the U.S. from 2010 to 2023 were diverse; nevertheless, the virotype F18:LT:STa:STb:Stx2e predominated and increased in frequency during this time period.